2006
DOI: 10.1002/ajim.20301
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between work permits, injury, and safety training among working teenagers

Abstract: Although teens with work permits were more likely to report receiving safety training than teens without permits, the occurrence of injury was no different among the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 10 publications
(9 reference statements)
2
20
1
Order By: Relevance
“…Barnetson (2013a) reported adolescent employment in Alberta at 43.7% in 2012. Similar levels are reported in the United States (Zierold and Anderson, 2006a;Zierold et al, 2004) and New Zealand (CARITAS, 2003).…”
Section: Child Labour In Developed Countriessupporting
confidence: 67%
“…Barnetson (2013a) reported adolescent employment in Alberta at 43.7% in 2012. Similar levels are reported in the United States (Zierold and Anderson, 2006a;Zierold et al, 2004) and New Zealand (CARITAS, 2003).…”
Section: Child Labour In Developed Countriessupporting
confidence: 67%
“…Although no prior studies have focused on fatalities among young landscapers, research has been conducted on non-fatal injuries. A study of high school students in Wisconsin found that only 55% of teenagers in tree trimming and cutting had work permits, compared to 70% among all employed teens [Zierold and Anderson, 2006]. The study did not find a difference in injury risk between teenagers with and without work permits, but workers without permits were less likely to report having received safety training.…”
Section: Agementioning
confidence: 96%
“…7,20,38,39 Furthermore, the substantial proportion of adolescents going to work without the proper permits is of particular concern in light of previous research showing that adolescents without work permits are less likely to be trained in workplace safety 40, 41 and more likely to be injured at work. 40…”
Section: Discussionmentioning
confidence: 99%